Determination of the Agricultural Mechanization Levels of the Enterprises Growing Pistachio (Pistacia vera L.): The Case of Siirt Province in Turkey - Metin AYGÜN; Songül GÜRSOY (Türkiye Tarımsal Araştırmalar Dergisi, 2020)
The objective of this study was to determine the agricultural mechanization properties of enterprises growing pistachio in Siirt province which is located in the Southeast Anatolia Region of Turkey. For this purpose, a survey was carried out in 165 selected enterprises by using a stratified random sampling method in 2019. Within the scope of the survey studies, the land size, tractors, and the number of agricultural machines in the enterprises growing pistachio in the region were examined and the current mechanization level of Siirt province was determined by considering these properties. As a result of the evaluation of the data obtained in the survey, it was determined that the number of tractors per enterprise was 0.43, the tractor engine power per enterprise was 22.51 kW, the average tractor power was 53.06 kW, the number of tools and machines per tractor and enterprise was 2.02 and 0.85, respectively, the average engine power per unit area was 3.38 kW ha-1, and the cultivated area per tractor was 15.69 ha. In conclusion, the number of equipment-machine per tractor and enterprise in pistachio producing farms was lower than the national average. It is possible to say that the small farm size and monoculture product pattern in the region significantly prevents the development of the level of mechanization.